Psalms 51-100 - Tate, Marvin E. (Word biblical commentary ;, 1990)
This work promises a fresh understanding of the last 50 of the Psalms, as well as a deeper appreciation of their impact, both in their original settings and in their continued history of interpretation throughout the generations.